Claudia and mean janine ebook - Telgemeier, Raina (Baby-Sitters Club Graphic Novel, 2016)
A graphic novel adapted and illustrated by Raina Telgemeier, the #1 New York Times bestselling, multiple Eisner Award-winning author of Smile ! Claudia and her sister, Janine, may as well be from two different planets. Claudia, who pays more attention to her artwork and The Baby-sitters Club than her homework, feels like she can't compete with her perfect sister. Janine studies nonstop, gets straight As, and even takes college-level courses! But when something unexpected happens to the most beloved person in their family, will the sisters be able to put aside their differences?